Impact of educational methods on the oral health literacy of Brazilian adolescents - Cristiane Caram Borgas Alves; Giuliana Martina Bordin; Marilisa Carneiro Leão Gabardo; Cristina Lúcia Feijó Ortolani (Revista Sustinere, 2026)
The assessment of oral health literacy (OHL) provides information that allows processing and understanding the presence of gaps in patients' basic health knowledge. This is a pre-post intervention study that evaluated the impact of educational approaches on the OHL level of adolescents aged 12 to 14 years from two private schools in São Paulo, Brazil. The sample consisted of 166 participants, who were divided into Group 1 (n = 45), who attended a lecture on oral hygiene; Group 2 (n = 44), who played an interactive educational game; Group 3 (n = 44), who participated in the oral hygiene lecture followed by the interactive game; and Group 4 (n = 33), who received no intervention. The BREALD-30 tool measured literacy initially (T0) and one month after the interventions (T1). OHL scores improved in Groups 1, 2, and 3 by 7%, 11.2%, and 16.4%, respectively. Pearson's test correlated the mean scores, and one-way ANOVA measured the influence of each educational method on OHL. The correlation test showed a robust coefficient (r = 0.80) for each group at the analyzed times. Analysis of variance indicated mean differences (p < 0.05) for the groups that received interventions when comparing T0 and T1. However, no significance (p > 0.05) occurred between groups and sex and between groups and school grades. The educational measures effectively increased OHL scores, and the lecture followed by the game was the best intervention.